In the garden of beasts : love, terror, and an American family in Hitler's Berlin - Larson, Erik (New York; Black Swan, 2012)
this book talks about Dodd and his family, notably his vivacious daughter, Martha, observe at first-hand the many changes - some subtle, some disturbing, and some horrifically violent - that signal Hitler's consolidation of power.
Keywords: Germany--Berlin; United States; Historians